Prognos vid kirurgisk behandling av kolik : en studie över 249 hästar under perioden 2002 till 2005 försäkrade i Agria - Müller, Sofia (SLU/Dept. of Clinical Sciences (until 231231), 2007)
In total 249 horses surgically treated for colic in Sweden during 2002 until 2005 were studied. The horses was identified by the animal insurance company Agria. Survival was studied with respect to age, gender, breed, diagnosis (small intestinal problems, caecal problems, large intestinal problems, incarceration in nephrosplenic ligament, unspecific colic and other colic problems) and treating hospital. Different survivals were calculated. For short-term survival proportions was used and for long-term it was done using Kaplan-Meier technique and log-rank testing. The overall short-term survival was defined as the horses that survived the stay at the clinic. Also the proportion that survived anaesthesia and the proportion that survived the clinic stay out of those that survived anaesthesia was determined. The long-term survival was mainly determined from the whole material but also on the horses that survived the clinic stay. The short-term survival in our study was 60%. Of the horses that went home from the clinic 91% was still alive after 1 year and after 2 and 3 years respectively the survivals were 87% and 80%. There were no differences in survival with respect to gender. However, there were differences in survival with respect to breed for total (long-term) survival. The racehorses had a worse survival, and the group with other horses had a significantly better survival compared to the rest of the breeds. The survival during the clinic stay for horses older than 13 years was worse compared to other groups. There were also significantly differences between the clinics concerning horses that were euthanized during anesthesia. The different colic diagnosis had a similar survival except for incarceration in nephrosplenic ligament (n=13). No horse died with this diagnosis during the clinic stay.